Pengelolaan Barang Inventaris Milik Daerah di Kota Makassar - Anggriani, Anggriani; Hakim, Lukman; Haerana, Haerana (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2025)
This study aims to ensure transparency, accountability, and efficiency in the management of regional inventory goods at the Makassar city regional secretariat office. By using a qualitative research method with a descriptive approach, it is intended to dig up as much information as possible from the research problem. Based on the results of the study, the management of regional inventory goods is in the form of: (1) data collection of regional inventory goods management that conducts an inventory of regional goods at least once a year. (2) In recording the management of regional inventory goods, it is usually done at least once a year to ensure the accuracy and sustainability of the data. However, some organizations may record more often. (3) As for the elimination of regional inventory goods management at the Makassar city regional secretariat office, it is proposed that the elimination process be managed by the regional financial and asset management agency. (4) Maintenance of regional goods is carried out periodically based on the condition of the goods proposed in a state that is not suitable for use or damaged within the scope of the regional secretariat. (5) As well as reporting regional inventory goods at the Makassar city regional secretariat office has been in accordance with the reporting based on the regulations that apply every year and semester.